Pengaruh Brand Image terhadap Keputusan Pembelian Konsumen - Aditya Julita Sari; IBN Udayana; Agus Dwi Cahya (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to determine the effect of "The Influence of Brand Image on Purchase Decisions Supported by Green Marketing and Brand Ambassador Variables on Moringa processed products and the Effect of Green Marketing and brand ambassadors on Brand Image". The type of research used is quantitative research and is included in explanatory research which in this study aims to explain the relationship of a variable with other variables to test hypotheses. Researchers also use questionnaires to obtain the data needed in the study. To obtain data, researchers used questionnaires which were distributed to consumers who know and become consumers of Moringa. The results in this study indicate that the brand image variable has a significant or positive influence on consumer purchasing decisions. The green marketing variable does not have a positive influence on consumer purchasing decisions. The brand ambassador variable has a significant influence on the consumer purchasing decision variables. The green marketing variable has a positive influence on the brand image variable. The brand ambassador variable has a positive influence on the brand image variable. Keywords: Brand Image, Green Marketing, Brand Ambassador, Purchase Decision, Significant